2021
DOI: 10.1149/2162-8777/abdfb7
|View full text |Cite
|
Sign up to set email alerts
|

Review—Photoluminescence Properties of Cr3+-Activated Fluoride Phosphors

Abstract: The Cr3+-activated phosphor properties are discussed in detail from an aspect of spectroscopic point of view. The host materials considered here are a various kind of fluoride compounds. The photoluminescence (PL) and PL excitation spectra of such Cr3+-activated fluoride phosphors are analyzed based on Franck−Condon analysis within the configurational-coordinate model. A method is proposed for obtaining reliable crystal-field (Dq) and Racah parameters (B and C) based on a general ligand field theory with payin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 106 publications
1
25
0
Order By: Relevance
“…The larger DE 1 and the smaller DE 2 mainly affect the thermal quenching at higher and lower temperatures, respectively. 78 As shown in Fig. 8b and Fig.…”
Section: Temperature Dependence Of Photoluminescence Propertiesmentioning
confidence: 59%
See 1 more Smart Citation
“…The larger DE 1 and the smaller DE 2 mainly affect the thermal quenching at higher and lower temperatures, respectively. 78 As shown in Fig. 8b and Fig.…”
Section: Temperature Dependence Of Photoluminescence Propertiesmentioning
confidence: 59%
“…Taking the radiative vibronic emissions and the nonradiative transition into consideration simultaneously, the temperature dependence of the PL intensity is proposed to be: 4,78…”
Section: Temperature Dependence Of Photoluminescence Propertiesmentioning
confidence: 99%
“…The luminescence properties of transition metal ions, such as Cr 3+ , originate from d–d electronic transitions, which are not shielded by the outer orbitals, unlike the 4f orbitals in trivalent lanthanide ions . Consequently, the spectroscopic characteristics of Cr 3+ ions are strongly affected by the crystal field strength of the matrix material; thus, the emission type, range, and thermal quenching rate can be tuned by changing the matrix type. The sensitivity of spectroscopic properties to the change of crystal field parameters plays a particular role in research on TM-based luminescence thermometers. ,, The irradiation with 405 nm wavelength excites a higher 4 T 1g level. The nonradiative energy transfer causes the increase in the population of the lowest vibrational level of 2 E g .…”
Section: Resultsmentioning
confidence: 99%
“…The Tanabe–Sugano diagram for d 3 suggested that these are 4 A 2g → 4 T 1g (P), 4 A 2g → 4 T 1g , and 4 A 2g → 4 T 2g transitions, respectively. Using the Tanabe–Sugano diagram for d 3 , the crystal field for ZnCrF 5 (H 2 O) 2 ( 5 ) was estimated as ∼15000 cm –1 (∼1.86 eV), which is in line with the reported Cr 3+ -activated fluoride phosphors . For Co 2+ - and Ni 2+ -based materials only two absorption bands originating from d–d transitions fall into the visible region, while low-energy 4 T 1g → 4 T 2g (Co 2+ ) and 3 A 2g → 3 T 2g (Ni 2+ ) transitions lie in the near-IR region and hence could not be observed with the available instrumentation.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Tanabe− Sugano diagram for d 3 , the crystal field for ZnCrF 5 (H 2 O) 2 (5) was estimated as ∼15000 cm −1 (∼1.86 eV), which is in line with the reported Cr 3+ -activated fluoride phosphors. 75 For Co 2+ -and Ni 2+ -based materials only two absorption bands originating from d−d transitions fall into the visible region, while low-energy 4 T 1g → 4 T 2g (Co 2+ ) and 3 A 2g → 3 T 2g (Ni 2+ ) transitions lie in the near-IR region and hence could not be observed with the available instrumentation. The typical Co-containing inverse weberite exhibits 4 T 1g → 4 A 2g (670−700 nm) and 4 T 1g → 4 T 2g (∼505 nm) bands.…”
Section: ■ Introductionmentioning
confidence: 97%